Integrasi Pendidikan, Teknologi, dan Pemberdayaan Ekonomi dalam Kegiatan KKN di Desa Tanjungjaya, Kabupaten Tasikmalaya - Selvy Isnaeni; Irsan Apriliawan; Ghevira Nurul Awaliyah; Aini Fadillah; Ula Aulia; Ai Linda Nurahmah (Universitas Perjuangan Tasikmalaya, 2026)
Community service activities through the Real Work Lecture (RWL) program in Tanjungjaya Village, Tasikmalaya Regency, were carried out to optimize existing potential. Tanjungjaya Village boasts favorable agroclimatic conditions and a rich cultural heritage, exemplified by the reog dog-dog art form. However, this potential has not been fully utilized due to technological limitations, low practitioner retention, and a lack of innovation. This activity uses a participatory approach with methods of community education, training, and mediation. The programs implemented include counseling on clean and healthy lifestyles, education on plastic waste recycling, socialization of disaster mitigation and tree planting to prevent landslides, and assistance to farmers to optimize agricultural cultivation as well as bridging the gap between farmers and extension workers and village officials regarding limitations in the field of agriculture. This activity also strengthens the partnership between universities and village governments and provides students with practical experience in applying their knowledge in the field. Overall, the community service program in Tanjungjaya Village has proven effective in encouraging community empowerment based on local potential towards independent and sustainable village development.